The Influence Of Job Satisfaction, Continued Commitment, And Work Environment On The Organisational Citizenship Behaviour Of Employees At The Special Region Of Yogyakarta Provincial Transportation Agency: - Usada, Dinda Theresia; Kurniawan, Ignatius Soni; Kusuma, Nala Tri (Universitas Dehasen Bengkulu, 2025)
The phenomenon of low employee voluntary behavior to go beyond their roles, or organizational citizenship behavior (OCB), remains a challenge in the government sector, including at the Department of Transportation of the Special Region of Yogyakarta. Low OCB can hinder the effectiveness of public services because employees only work according to their job descriptions without making extra contributions. Based on the differing findings of previous research regarding factors influencing OCB, this study was conducted to examine the influence of job satisfaction, continuous commitment, and work environment on OCB. This study employed a quantitative approach with a population of 50 employees, who were also used as the sample through a census technique. Data was collected using a five-point Likert scale questionnaire, then analyzed with multiple linear regression using SPSS. The research results show that job satisfaction, continuous commitment, and work environment have a positive and significant effect on OCB. These findings support the social exchange theory (SET) framework, which asserts that reciprocal interactions between employees and the organization encourage the emergence of extra-role behavior. The practical implications of this research emphasize the importance of increasing job satisfaction, strengthening employee commitment, and creating a conducive work environment to enhance OCB and support organizational performance.